DIFFERENCES IN HDL AND TRIGLYCERIDE LEVELS IN OBESE AND NORMAL WEIGHT PATIENTS WITH METABOLIC SYNDROME: A LITERATURE REVIEW - Ramadhan, Muhammad Zidan; Rakhmat, Iis Inayati; Yuslianti, Euis Reni (Fakultas Kedokteran Universitas Jenderal Achmad Yani, 2025)
Metabolic Syndrome (MS) is a cluster of complex metabolic disorders characterized by central obesity, insulin resistance, dyslipidemia, and hypertension, which collectively increase the risk of cardiovascular disease. One important indicator of dyslipidemia is the triglyceride-to-high-density lipoprotein (HDL) ratio, where elevated triglycerides and reduced HDL levels reflect an imbalance in lipid metabolism. The risk of MS is not only found in obese individuals but also in those with normal body weight (metabolically obese normal-weight individuals), indicating that visceral fat distribution, genetic factors, and lifestyle also play a role. This literature review aims to examine differences in HDL and triglyceride levels in MS patients with obesity and normal body weight. Articles were searched through PubMed, DOAJ, Google Scholar, and GARUDA databases within the last 10 years using relevant keywords. Of the 18 articles that met the inclusion criteria, the review showed a consistent pattern indicating that individuals with MS, whether in the obese or normal-weight groups, exhibited elevated triglyceride levels accompanied by significantly reduced HDL levels. These findings highlight that lipid abnormalities represent a central mechanism in MS that contributes to the risk of atherosclerosis and cardiovascular disease, regardless of body weight status. In conclusion, this review demonstrates that there are differences in triglyceride and HDL levels among MS patients with obesity and those with normal body weight, suggesting that lipid profile evaluation should be a primary focus in cardiometabolic disease prevention strategies. Keywords: dyslipidemia, high-density lipoprotein (HDL), obesity, metabolic syndrome, triglycerides DOI : 10.35990/mk.v8n4.p423-433